Pengaruh Fokus Masa Depan Dan Motivasi Otonom Dalam Perilaku Pencarian Kerja Terhadap Wawancara Kerja - Yarsono, Hendi; Abadi, Ferryal (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study aims to provide an understanding of the factors that encourage job seekers during a job search to be able to identify their potential and behavior and actions in the job search process to get a job. The data collection method used is through an online survey with a total of 120 respondents and the population is job seekers who are domiciled in Jabodetabek with the sample criteria being job seekers who have graduated at least high school level/equivalent with an age range of 17-64 years. Structural equation model (SEM) analysis method was used in testing this research model. The results found that focus on the future has a positive effect on job search intensity and job search quality. For autonomous motivation has a positive influence on the intensity of job search and job search quality. While the intensity of job search does not have a significant effect on job interviews. On the quality of job search has a positive influence with job interviews. From the test results, it is suggested that job seekers should be encouraged to focus on what they have learned from their involvement in various job search activities. Autonomous motivation is needed to help job seekers face difficulties during job search.